1967
DOI: 10.1111/j.1365-2141.1967.tb08866.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte Folate in Vitamin B12 and Folate Deficiency and in Leukaemia

Abstract: SUMMARY Leucocyte folate concentrations were measured in 24 normal subjects, in 32 patients with subnormal serum folate concentrations and normal serum B12 concentrations associated with chronic gastro‐intestinal disease, in seven patients with leukaemia, and in 10 patients with untreated pernicious anaemia. In the normal subjects, the leucocyte folate levels ranged from 60 to 123 ng./ml. of packed leucocytes. Among the patients with subnormal serum folate concentrations, leucocyte folate concentrations were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The total folate concentrations in leucocytes found here are substantially similar to those reported previously (Swendseid, Bethell & Bird, 1951;Hoffbrand & Newcombe, 1967). The generally higher L. casei activity than S. faecalis activity suggests that, in most cases, methylfolates comprise a major proportion of leucocyte folate but there was no consistent difference in ratio of these two micro- biological activities according to the type of leukaemia or the degree of primitiveness of the cells.…”
Section: Discussionsupporting
confidence: 89%
“…The total folate concentrations in leucocytes found here are substantially similar to those reported previously (Swendseid, Bethell & Bird, 1951;Hoffbrand & Newcombe, 1967). The generally higher L. casei activity than S. faecalis activity suggests that, in most cases, methylfolates comprise a major proportion of leucocyte folate but there was no consistent difference in ratio of these two micro- biological activities according to the type of leukaemia or the degree of primitiveness of the cells.…”
Section: Discussionsupporting
confidence: 89%
“…Swendseid et a1 [21] measured leucocyte folate by microbiologic assay, reporting average values of 80 ng/ml of packed cells, and indicated that the leucocytes themselves contained sufficient conjugase to hydrolyze all of their own folate. Hoffbrand and Newcombe [8] confirmed that addition of conjugase to leucocyte suspensions before sonication did not significantly alter the mean microbiologic folate activity of these cells. The leucocyte folate levels in normal subjects were similar to those previously reported (60-123 nglml), but they were subnormal in all patients whose marrow showed giant metamyelocytes or obvious megaloblastic changes.…”
Section: Lymphocyte Dumentioning
confidence: 80%
“…Although the precise significance of this localized defect is not yet clear, it suggests that selective nutrient deficiency may occur in one but not another cell line competing for limited available nutrients in the same subject. It should be noted that the concept of a folate deficiency state localized to a particular cell line goes back at least as far as the reports of Newcombe (1966) andLindenbaum et al(1975), which have been summarized by Lindebaum (1977).…”
Section: Discussionmentioning
confidence: 98%